The Effect of Refresher Training on Air Traffic Controllers Performance at Jakarta ACC Unit - Nora Uzatul Jannah; Emilia Rahajeng Larasati; Dhian Supardam (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The Indonesian aviation industry has experienced rapid growth following the post-pandemic recovery, resulting in increased operational demands for air traffic control services, particularly at the Jakarta Air Traffic Service Centre (JATSC). This study aims to analyze the effect of refresher training on the performance of Air Traffic Controllers (ATCs) at JATSC and to identify factors influencing its effectiveness. Using a quantitative approach with a quasi-experimental design, the study involved 70 licensed ATCs with a minimum of two years of experience, selected through simple random sampling. The independent variable, refresher training, was assessed through content quality, instructional methods, duration, instructor competence, and evaluation mechanisms, while ATC performance was measured across operational safety, efficiency, technical competence, and knowledge retention. Data were collected using a structured questionnaire and analyzed descriptively and inferentially. The results revealed that refresher training had a significant positive impact on ATC performance, especially in enhancing communication effectiveness, safety compliance, and technical proficiency. However, participants perceived the training duration as insufficient for complex simulation practices. The study concludes that well-structured refresher training contributes substantially to maintaining controller competence and operational safety at JATSC, emphasizing the need for continuous improvement in training design and implementation